Study of Some Biochemical and Hematological Parameters Changes of Wistar Rats Blood Parallel to Oral Nanosilver Consumption - MH Razavian (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Nano particles because of the marvelous anti–microbe effects and increasing consumption in different industries are part of the most usable of these particles which this has increased the necessity of the study on the safety of using these materials. The aim of this study was to examine the effects of time and consumption dose of these particles on the some biochemical and blood parameters of rats of wistar race. METHODS: Thirty six Wistar race rats after 4 week similarization period divided to 6 groups of 6 rats (one control and five tests). Nanosilver (nanocid L2000) solution was purchased from NanoNasb-e-Pars Co and 95PPm, 65PPm, 35PPm, 20PPm and 5PPm concentrations were prepared. Then above solutions were used as water for 6 months. Three rats of each group were randomly selected after 3 and 6 months and biochemical parameters, Hb and HCT was measured and compared in different groups. FINDINGS: There are no significant changes in the rats blood cholesterol and sugar in the form of dose/time dependent manner in spite the fact that increasing the blood sugar level in all doses specially 35PPm after six months was considerable. The blood triglyceride level showed significantly decrease both in synchronic (p<0.01 after 3 months and p<0.05 after 6 months) and dose dependent (decreasing with p<0.01) manner. Lowering of triglyceride in 35PPm was considerable again. Counting the white blood cells shows dose dependent decreasing in number of these cells (p<0.001). No tangible change was seen on counting of red blood cells and measuring Hb and HCT parameters.CONCLUSION: The results of this study showed that oral consumption of nanosilver particles especially in high doses and long terms causes not only damage to the liver but also decrease the number of white blood cells (WBCs) and immunity level of the organism.